DARI POLITIS KE KULTURAL: TRANSFORMASI NILAI RUANG KAWASAN KEPATIHAN SURAKARTA: From Politic to Cultural: Transformation of Spatial Values in Kepatihan Surakarta Area - Arnindya Afifah Urfan; Sudaryono, Sudaryono (Jurusan Teknik Perencanaan Wilayah dan Kota, Fakultas Sains dan Teknologi, Universitas Islam Negeri Alauddin Makassar, 2024)
One of the locations that had a great deal of urgency during the Surakarta Palace era is the Kepatihan district, where the Kepatihan Institution put the government system into place. This region was burned by the unrest that followed the incident with Indonesian independence in Surakarta. In addition to being a neighbourhood with offices and residences, this area was also referred to as a